Evaluating the efficacy of active reading software in enhancing EFL learners’ reading comprehension skills - Khan, Imran; Ainol Haryati, Ibrahim; Asiah, Kassim; Khan, Raja Muhammad Ishtiaq (International Journal of Scientific and Technology Research, 2019)
Reading ability of the learners plays a pivotal role in their academic success. Reading without comprehension affects learners’ learning outcomes. However, the development of learners’ reading ability has always been a great challenging task for language teachers. The efficacy of computer-assisted language (CALL) in improving language skills has been endorsed by many studies under different socio-cultural settings. However, in Saudi EFL context, using CALL in teaching and learning languages is still scarce and there are more for researchers to explore. The current study intended to examine the effects of Active Reading Software (ARS) on reading comprehension skills of Saudi EFL learners at tertiary level. A quasiexperimental study was carried out at Majmaah University involving 30 EFL learners, which were equally clustered into a control group and an experimental group. A four- week treatment incorporating the ARS was assigned to the experimental group, while the control group received the same learning materials in a traditional classroom setting. Data acquired from the study were evaluated using t-test. Findings revealed a substantial difference between the mean scores of the two groups in terms of reading comprehension; the experimental group outperformed the control group. These results indicate that utilizing ARS can further enhance the EFL learners’ reading comprehension skills and thus, it can be assumed that the ARS software can be a facilitative learning tool in the teaching and learning of reading.